2022
DOI: 10.3233/cbm-210264
|View full text |Cite
|
Sign up to set email alerts
|

Association of SIRT1 single gene nucleotide polymorphisms and serum SIRT1 levels with laryngeal squamous cell carcinoma patient survival rate

Abstract: BACKGROUND: SIRT1 is a multifunctional protein, possibly essential in tumorigenesis pathways, which can act both as a tumor promoter and tumor suppressor depending on the oncogenes, specific to particular tumors. Pathogenesis of laryngeal cancer is multifactorial and the association of SIRT1 expression with the clinical characteristics and prognosis of LSCC has not been fully identified. OBJECTIVES: The study aimed to evaluate associations between single gene nucleotide polymorphisms (SNPs) of SIRT1 (rs3818292… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…It also hindered EMT in OSCC by suppressing Smad2/3 phosphorylation and Smad4 deacetylation [84]. Disruption of SIRT1-induced deacetylation of c-JUN by miR-135b-5p promoted migration and invasion in NPC cells [85]. The Kaplan-Meier survival analysis further demonstrated that patients with increased levels of SIRT1 experienced significantly prolonged overall survival, as indicated by Logrank p < 0.05 (Fig.…”
Section: Class III Hdacsmentioning
confidence: 79%
See 2 more Smart Citations
“…It also hindered EMT in OSCC by suppressing Smad2/3 phosphorylation and Smad4 deacetylation [84]. Disruption of SIRT1-induced deacetylation of c-JUN by miR-135b-5p promoted migration and invasion in NPC cells [85]. The Kaplan-Meier survival analysis further demonstrated that patients with increased levels of SIRT1 experienced significantly prolonged overall survival, as indicated by Logrank p < 0.05 (Fig.…”
Section: Class III Hdacsmentioning
confidence: 79%
“…SIRT1 expression was found to be predominant in cases involving patients aged over 65 years, lymph node negative and early clinical stage cases for HNSCC [86], suggesting its potential as a valuable prognostic assessment tool. The single gene nucleotide polymorphisms (SNPs) in SIRT1 were linked to the survival rate of LSCC patients [85]. Notably, the SIRT1 rs3758391 T/T genotype demonstrated a significant association with an elevated likelihood of developing LSCC [85].…”
Section: Class III Hdacsmentioning
confidence: 99%
See 1 more Smart Citation
“…The following study also proved that the two SIRT1 rs1467568 and rs7895833 polymorphisms had an impact on the reduced risk of developing CRS1 in the Chinese population [ 26 ]. In the work of Vaiciulis et al, which focused on the study of laryngeals squamous cell carcinoma (LSCC) development probability, carriers of the SIRT1 rs3758391 T/T genotype had a statistically significant increased probability of developing advanced-stage LSCC, according to the codominant and recessive genetic model (OR = 2.387; 95% CI = 1.091–5.222; p = 0.029 and OR = 2.287; 95% CI = 1.070–4.888; p = 0.033, respectively) [ 27 ]. In contrast, in our study, we found no statistically significant differences in the development of periodontitis in the male population in our study.…”
Section: Discussionmentioning
confidence: 99%